Patient Blood Management in Europe - Shander, A.; Van Aken, H.; Colomina, M.; Gombotz, H.; Hofmann, Axel; Krauspe, R.; Lasocki, S.; Richards, T.; Slappendel, R.; Spahn, D. (Oxford University Press, 2012)
Preoperative anaemia is common in patients undergoing orthopaedic and other major surgery. Anaemia is associated with increased risks of postoperative mortality and morbidity, infectious complications, prolonged hospitalization, and a greater likelihood of allogeneic red blood cell (RBC) transfusion. Evidence of the clinical and economic disadvantages of RBC transfusion in treating perioperative anaemia has prompted recommendations for its restriction and a growing interest in approaches that rely on patients' own (rather than donor) blood. These approaches are collectively termed ‘patient blood management’ (PBM). PBM involves the use of multidisciplinary, multimodal, individualized strategies to minimize RBC transfusion with the ultimate goal of improving patient outcomes. PBM relies on approaches (pillars) that detect and treat perioperative anaemia and reduce surgical blood loss and perioperative coagulopathy to harness and optimize physiological tolerance of anaemia. After the recent resolution 63.12 of the World Health Assembly, the implementation of PBM is encouraged in all WHO member states. This new standard of care is now established in some centres in the USA and Austria, in Western Australia, and nationally in the Netherlands. However, there is a pressing need for European healthcare providers to integrate PBM strategies into routine care for patients undergoing orthopaedic and other types of surgery in order to reduce the use of unnecessary transfusions and improve the quality of care. After reviewing current PBM practices in Europe, this article offers recommendations supporting its wider implementation, focusing on anaemia management, the first of the three pillars of PBM.